The Development of Pop-up Book on the Role of Buffer in the Living Body - Sari, Sri Adelila; Azzah Ulya (European Journal of Social Science Education and Research, 2019)
The aims of this research were to: (i) develop a pop-up book on the role of buffer in the living body for senior high school, and (ii) describe the response of learners and teachers to the developed pop-up book. The method of research was a Research and Development (R - D) with a model ADDIE (Analysis, Design, Development, Implementation and Evaluation). Phase of analysis was done by interviewed the teacher and distributed questionnaires to the needs analysis to 26 learners of senior high school, named SMAN 3 Banda Aceh. The design phase included the activities of the material formulation, the determination of media design (theme, colors and images) and manufactured of blueprints pop-up book that would be validated. The development phase was done by manufactured of pop-up book as designed and carried out feedback from the expert validators. At the implementation stage, the learning process was conducted using the developed pop-up book to study the response of learners and teachers on the book. In the evaluation phase, the successfulness of development of a pop-up book using ADDIE models was determined. Based on the results of the feasibility assessment of pop-up book, the responses of learners and teachers noted that pop-up book has been successfully developed with the average percentage of 94.047 percent and the feasibility of obtaining the category of very decent. The percentage of response’ learners reached 92 percent and the percentage of chemistry teacher’s response was found to be 80 percent. Obtaining this percentage was in excellent condition, so that it could be said that the students and the teacher to respond strongly agreed that the developed pop-up book could be accepted as an alternative medium of learning the material role of buffer solution in the living body.